Pengujian Karakteristik Perpindahan Panas dan Penurunan Tekanan dari Sirip-Sirip Pin Diamond Susunan Segaris dalam Saluran Segiempat - Tri Istanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2010)
This research was conducted to investigate the characteristics of heat transfer and pressure drop as well as the thermal performance of diamond pin fin array in the rectangular channel which air was passed through it as coolant fluid. The pin fins were arranged in inline manner. Dimension of base plate in which pin fins attached was 150 mm x 200 mm x 6.5 mm. The average temperature of base plate surface was kept constant at 60oC. Pin fins were made of duralumin having the dimension of 75 mm of height, its sides 12.7 and 12.7 mm respectively, and the distance inter-fin picth in the spanwise direction was kept constant at Sx/D = 2.95. The parameters of this research were Reynolds number (Re) 3,123 – 37,847 based on averaged inlet air velocity and hydraulic diameter, and the distance between the inter-fin pitch in the streamwise direction (Sy/D = 1.97 – 3.94). The research result shown that increasing Reynolds and decreasing the distance Sy/D increased Nusselt number, that means increased heat transfer rate where it reach maximum at Sy/D = 2.36. The values of pressure drop (DP) and friction factor (f) decreased with increasing Sy/D. The value of the thermal performances (h) varied between 0.77 – 1.22. At Sy/D = 1.97 for Re > 25,000, and Sy/D = 3.94 for all values of Re, the values of h were less than 1, i.e. the used of diamond pin fin would cause an energy loss rather than gain. The net energy gain (h was greater than 1) was only at Sy/D = 1.97 for Re < 18,830, Sy/D = 2.36 for Re < 25,000 and at Sy/D = 2,95 for Re < 3,150. Increasing Reynolds number would decrease the thermal performance (h) for all Sy/D. A net energy gain up to 22% was achieved for Sy/D = 2.36 and Re = 3,123. Keywords: diamond pin fin, Reynolds number, friction factor, thermal performance